Unveiling agroecological transitions in Northern Patagonia: a comparative typology approach - Álvarez, Valeria Esther; El Mujtar, Verónica Andrea; Cardozo, Andrea Gabriela; Sisón Cáceres, Leandro Áxel; Heinzle, Leila Yamila; Castán, Elisa; Tittonell, Pablo Adrián (Frontiers in Agronomy, 2025)
IntroductionAgroecological transitions are complex, multidimensional processes that require analytical tools capable of capturing contextual and systemic diversity. Typology construction has proven valuable for characterizing the heterogeneity of farming systems and supporting the design of agroecological transformation pathways.MethodsThis study applies a comparative typology approach in the Comarca Andina del Paralelo 42 (CAP42), a mountainous forest region of Northern Patagonia, Argentina. We analyzed 53 small- and medium-scale farms (median area: 13 ha) representing diverse production systems, including fruit and/or vegetable growing, livestock, and mixed farming. The Tool for Agroecology Performance Evaluation (TAPE) was used to assess the agroecological transition level of each farm. Data derived from TAPE were analyzed using two complementary multivariate methods: Archetypal Analysis and Reinert’s Descending Hierarchical Classification.ResultsBoth methods effectively captured meaningful patterns of diversity in the configuration of the Elements of Agroecology, enabling the identification of representative farm types. Archetypal Analysis revealed hybrid or transitional profiles and subtle intra-group variations, while Reinert’s classification generated distinct and interpretable clusters. The resulting typology comprised four groups—Agroecology Keepers, Community Pillars, Social Weavers, and Agroecology Seekers—reflecting the diversity and socially driven nature of agroecological change in the CAP42 region.Discussion and ConclusionsThis study demonstrates the potential of typology-based approaches to enhance both analytical depth and practical relevance in agroecological research. By combining interpretability and complexity, the proposed methodology provides a robust framework for understanding diverse transition pathways. Further research exploring the main barriers and drivers of change will deepen understanding of the detected patterns and clarify the influence of territorial context on the dynamics of agroecological transitions in Northern Patagonia.